2006
DOI: 10.1897/05-552.1
|View full text |Cite
|
Sign up to set email alerts
|

The use of in situ and stream microcosm experiments to assess population‐ and community‐level responses to metals

Abstract: We conducted field and stream microcosm experiments to assess population-level (density, size distribution) and community-level (species richness metrics, multivariate analysis of community composition) responses of macroinvertebrates to heavy metals in the Arkansas River, a mining-polluted stream in Colorado, USA. Experiments were conducted in spring and summer to coincide with early and late developmental stages (i.e., instars) of the mayfly Rhithrogena hageni. Results of field experiments showed significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 43 publications
2
51
0
Order By: Relevance
“…Our studies identified the genus Ephemerella and two heptanegiid mayflies as being particularly susceptible to dissolved Cd. These findings give mechanistic support to observations that these taxa are consistently absent from metal-contaminated habitats in nature (40) and are consistently more sensitive to metals in sophisticated toxicity tests (39)(40)(41). The presence of a relatively strong phylogenetic signal associated with the integrated trait of ''sensitivity to dissolved Cd'' suggests that sensitivity to metals may eventually be predictable on the basis of phylogenetic position, as described above.…”
Section: Discussionsupporting
confidence: 78%
“…Our studies identified the genus Ephemerella and two heptanegiid mayflies as being particularly susceptible to dissolved Cd. These findings give mechanistic support to observations that these taxa are consistently absent from metal-contaminated habitats in nature (40) and are consistently more sensitive to metals in sophisticated toxicity tests (39)(40)(41). The presence of a relatively strong phylogenetic signal associated with the integrated trait of ''sensitivity to dissolved Cd'' suggests that sensitivity to metals may eventually be predictable on the basis of phylogenetic position, as described above.…”
Section: Discussionsupporting
confidence: 78%
“…Winner et al [44] observed seasonal variation in the sensitivity of zooplankton communities to Cu exposure. Similarly, mesocosm experiments conducted with macroinvertebrate communities showed that summer communities, which were dominated by smaller, early instars of aquatic insects, were more sensitive to metals than communities collected in late spring [45], which were dominated by larger individuals. These investigators suggested that phenology and life history characteristics of sensitive resident species should be considered when designing biomonitoring programs and establishing water quality criteria.…”
Section: Temporal Variation In Contaminant Effectsmentioning
confidence: 96%
“…The concentration-response relationships between heavy metals and R. hageni density, species richness, mayfly richness and EPT were established, wherein different sensitivities might exist due to the phenology and developmental stage influencing responses of some aquatic macroinvertebrates to metals. Timing bioassessments to coincide with the presence of these sensitive life stages can improve the ability to detect subtle contaminant effects [122]. The taxa richness for aquatic benthic insect community can be used to indicate the impact of acid mine drainage in a tropical Asia stream [123].…”
Section: Population-and Community-level Approachesmentioning
confidence: 99%